ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN VARIABEL MEDIASI KEPUASAN PELANGGAN (Studi pada Industri Rumah Tangga Jamu Putri Ayu Semarang) - Vincentia Chrysanti Ayu Kurnia Asri; Bambang Munas Dwiayanto (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of service quality on customer satisfaction and loyalty with customer satisfaction as a mediator variable in the home industry of Jamu Putri Ayu. The sample used in this study was the people of Semarang City who had consumed the Jamu Putri Ayu product in the last one year. The sample used in this study were 158 respondents. The sample collection method is purposive sampling. The data collection method was the distribution of online questionnaires via google form. This research used Structural Equation Modeling (SEM) with AMOS 22 analysis tool. The result of this study found that customer satisfaction has a positive and significant effect on customer loyalty. In addition, service quality has no influence on customer satisfaction and customer loyalty. Also, in this study, customer satisfaction cannot mediate service quality with customer loyalty.